The Effect of Corporate Social Responsibility (CSR) Disclosure and Political Connection on Corporate Tax Avoidance: A Study from Indonesia’s Mining Sector Listed Companies - Kinanti Ranum Falina; Retno Yuni Nur Susilowati (International Journal of Economics, Management and Accounting, 2026)
This study investigates the effect of Corporate Social Responsibility (CSR) disclosure and political connection on corporate tax avoidance among mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. As CSR practices increasingly shape stakeholder expectations, questions arise as to whether such disclosures genuinely reflect ethical corporate behavior or are strategically employed to legitimize tax planning. In addition to CSR disclosure, political connection is examined as an external institutional factor that may influence firms’ tax behavior by reducing regulatory scrutiny and enforcement risk. CSR disclosure is measured using the Global Reporting Initiative (GRI) index, while tax avoidance is proxied by the Effective Tax Rate (ETR). Additionally, political connection is identified based on the presence of politically affiliated individuals in the firms’ board list. This study adopts a quantitative approach employing panel data linear regression analysis. The research population consists of mining companies consistently listed on the IDX during the observation period, with samples selected through purposive sampling, having 41 mining companies in total. This study aiming to contribute to academic discourse and practical implications for policymakers, investors, and regulators. The findings found that there are no significant effect between CSR disclosure and political connection on tax avoidance. The results of this study concluded that there are many factors both from internal and external that could affect tax avoidance activity in Indonesia’s mining companies yet was not covered in this study.